Sequence paleogeography and coal accumulation model in the fluvio-lacustrine rift basin: The Lower Cretaceous of the Huhehu Sag of Hailar Basin, Inner Mongolia (NE China). (November 2022) - Zhu, Mingyu; Shao, Longyi; Sun, Bin; Yao, Haipeng; Spina, Amalia; Ma, Shimin; Wang, Shuai; Fan, Jinyun; Li, Jian-An; Yan, Sheng
Abstract: Significant volumes of coals can be preserved in fluvio-lacustrine rift basins but prediction of occurrence and geometry within a sequence-stratigraphic framework is always a challenge. The Huhehu Sag is a continental rift basin in Hailar Basin of NE China, with the Damoguaihe and Yimin formations of Lower Cretaceous as the main coal-bearing strata. In this study, the sedimentary facies, sequence stratigraphy, paleogeography, and coal accumulation characteristics in the Huhehu Sag are analyzed. Data used includes boreholes, geophysical well logs and seismic profiles. The coal-bearing strata are mainly composed of conglomerates, sandstones, siltstones, mudstones, and coals. Alluvial fan, braided fluvial, fan delta, braided fluvial delta and lacustrine depositional systems are identified. Coal seams were mainly formed in lacustrine and delta depositional systems. Six third-order sequences were subdivided according to sequence boundaries represented by regional unconformities, basal surfaces of incised valley fills, facies-reversal surfaces, and abrupt color changes related to the base level changes. Sequence 1 corresponds to the Tongbomiao Formation formed in the early syn-rift phase, Sequence 2 corresponds to the Nantun Formation formed in the syn-rift climax phase, Sequence 3 and 4 span the Damoguaihe Formation, with Sequence 3 formed in the syn-rift climax phase and Sequence 4 formed in the late syn-rift phase, and Sequence 5 and 6 span the Yimin Formation which were formed in the post-rift stage. All six sequences were developed with littoral-sublittoral lake, delta front and delta plain paleogeographic units. Sequence 1 to Sequence 2, Sequence 3 to Sequence 4 and Sequence 5 to Sequence 6 are of progradational patterns, while Sequence 2 to Sequence 3 and Sequence 4 to Sequence 5 display retrogradational features. From Sequence 1 to Sequence 4, the syn-rift led to the thickening of strata as well as the coal seams towards the eastern side of the sag. In Sequence 5 and 6, post-rift thermal sagging caused the wide distribution of the strata with the depositional centers as well as the thick coals being distributed in the central belt of the sag. Coals were mainly developed in the transgressive systems tract (TST) and highstand systems tract (HST) of Sequences 4 and 5. The favorable paleogeographic units for thick coal accumulations were mainly littoral-sublittoral lacustrine and delta. The Huhehu Sag is interpreted as an overfilled basin, we further divided the overfilled basin into three subtype basins by accommodation space, including the low, moderate, and high accommodation overfilled basins. In the low accommodation overfilled basin, the relatively thick coals were developed near the maximum flooding surface, while in the moderate accommodation overfilled basin, the relatively thick coals were developed in the lower-middle part of TST and the middle part of HST. These results could be used to predict the preferred depositional environments and favorable areas for coal and coalbed methane exploration in the fluvio-lacustrine rift basins. Highlights: Coal accumulation in fluvio-lacustrine rift basin represented by Huhehu Sag was studied. Syn-rift stage is associated with thickening of Sequence 1 to 4 and coals towards the foot wall side of the sag. Post-rift thermal sagging led to thickening of Sequence 5 to 6 and coals towards the central belt of the sag. Overfilled basin characterized for this sag has low, moderate, and high accommodation subtypes. These three subtypes of overfilled basin show different distribution patterns of thick coals.